Breakpoint :why the web will implode, search will be obsolete, and everything else you need to know about technology is in your brain - Stibel, Jeffrey M. (Palgrave Macmillan, 2013)
"What can the human brain and its relationship to the internet tell us about our society, our technologies, and our businesses? A lot, as it turns out. The internet today is a virtual replica of the brain, and the networks that leverage it grow and collapse in ways that are easily predictable if you understand the brain and other biological networks. We're living in the midst of a networking revolution. All of the major technology innovations of the 21st century - social networking, cloud computing, search engines, and crowdsourcing, to name a few - leverage the internet and are thus bound by the rules of networks. We've seen the exponential growth of these technologies, and they've led to a more efficient and tightly connected world. But what many people don't realize is that all networks eventually reach a breakpoint and collapse. This happens in the brain, it happens in nature, it happened to MySpace, and it will happen to Facebook and Google. It is critical to understand where the breakpoint is in the networks you use in order to achieve optimum success. Navigating the world of new technologies today can be like walking through a minefield unless you know the path. Imagine what you could do with a roadmap for where things are headed? In this fascinating look at the future of business and technology, neuroscientist and entrepreneur Jeff Stibel shows how the brain can act as a guide to understanding the future of the internet and the constellation of businesses and technologies that run on it. He'll show how leaders like Marissa Mayer are using artificial intelligence to literally remake Yahoo! and how startups like oDesk and Kickstarter are using crowdsourcing, the next wave of revolutionary technology, to create something much larger and "smarter" than the sum of their parts. Stibel offers a fresh perspective about the future of business and technology in a candid and engaging manner"--